A Gravitational-wave-detectable Candidate Type Ia Supernova Progenitor - Emma T. Chickles; Kevin B. Burdge; Joheen Chakraborty; Vik S. Dhillon; Paul Draghis; James Munday; Saul A. Rappaport; John Tonry; Evan B. Bauer; Alex J. Brown; Noel Castro; Deepto Chakrabarty; et al. (The Astrophysical Journal)
Type Ia supernovae (SNe Ia), critical for studying cosmic expansion, arise from thermonuclear explosions of white dwarfs, but their precise progenitor pathways remain unclear. Growing evidence supports the “double-degenerate scenario,” where two white dwarfs interact. The absence of nondegenerate companions capable of explaining the observed SN Ia rate, along with observations of hypervelocity white dwarfs, interpreted as surviving companions of such systems, provide compelling evidence for this scenario. Upcoming millihertz gravitational-wave observatories like the Laser Interferometer Space Antenna (LISA) are expected to detect thousands of double-degenerate systems, though the most compact known candidate SN Ia progenitors produce marginally detectable signals. Here, we report observations of ATLAS J1138-5139, a binary white dwarf system with an orbital period of just 28 minutes. Our analysis reveals a 1 M _☉ carbon–oxygen white dwarf accreting from a high-entropy helium-core white dwarf. Given its mass, the accreting carbon–oxygen white dwarf is poised to trigger a typical-luminosity SN Ia within a few million years, to evolve into a stably transferring AM Canum Venaticorum (or AM CVn) system, or undergo a merger into a massive white dwarf. ATLAS J1138-5139 provides a rare opportunity to calibrate binary evolution models by directly comparing observed orbital parameters and mass-transfer rates closer to merger than any known SN Ia progenitor. Its compact orbit ensures detectability by LISA, demonstrating the potential of millihertz gravitational-wave observatories to reveal a population of SN Ia progenitors on a Galactic scale, paving the way for multimessenger studies offering insights into the origins of these cosmologically significant explosions.